Evaluation of clinical diagnosis of children with acute appendicitis at Rapareen Teaching Hospital - Kaka, Wesam Amjad; Chalabi, Dlair A. K. (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objectives: Appendicitis is the most common acute surgical emergency of childhood. Decision-making in patients with acute appendicitis poses a diagnostic challenge worldwide. Among the reported diagnostic criteria, modified Alvarado score system and ultrasound findings where used to support diagnosis and even exclude complicated cases. The aim of this study was to detect clinical and sonograghic features that distinguish children visited the emergency department with acute simple appendicitis and idntify factors related to complicated cases. Methods: This cross-sectional study included 76 children with the provisional diagnosis of acute appendicitis according to clinical findings attending the Emergency Departement at Rapareen Teaching Hospital in Erbil between January and December 2012. Results: Of 76 patients included in this study, 75 patients (99.7%) had appendicitis whether inflamed (63 patients, 82.9%) or complicated (13 patients, 15.8%) and only one patient had normal operative (non-inflamed appendix) findings. Delay of admission, high temperature at time of presentation, localized tenderness and MASS of ≥ 7 increased the risk of complicated appendicitis as do leukocytosis and positive ultrasound findings. Conclusion: The study shows that use of certain clinical data (like duration of manifestations) with the modified Alvarado score system supported by leukocytosis and positive ultrasound findings in children suspected to have acute appendicitis provides a high degree of diagnostic accuracy of complicated cases rather than simple acute appendicitis